2017
DOI: 10.1016/j.taap.2017.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the toxicity of sintered and unsintered indium-tin oxide particles in murine macrophage and epidermal cells

Abstract: Indium-tin oxide (ITO) is used to produce flat panel displays and several other technology products. Composed of 90% indium oxide (InO) and 10% tin oxide (SnO) by weight, ITO is synthesized under conditions of high heat via a process known as sintering. Indium lung disease, a recently recognized occupational illness, is characterized by pulmonary alveolar proteinosis, fibrosis, and emphysema. Murine macrophage (RAW 264.7) and epidermal (JB6) cells stably transfected with AP-1 to study tumor promoting potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Sn is reported to possess antimicrobial activities and has been widely used as a promising dopant with oxides like, In 2 O 3 and ZnO, for enhancing the antimicrobial, electrical, optical and structural properties [11][12][13][14] . There are several reports which suggested that ITO possess toxicity action on the cells and organs [15][16][17][18][19][20] . However, the database on deep and persistent toxicity, carcinogenicity, genotoxicity, reproductive toxicity, besides skin or eye irritation and sensitization is very inadequate or even missing.…”
mentioning
confidence: 99%
“…Sn is reported to possess antimicrobial activities and has been widely used as a promising dopant with oxides like, In 2 O 3 and ZnO, for enhancing the antimicrobial, electrical, optical and structural properties [11][12][13][14] . There are several reports which suggested that ITO possess toxicity action on the cells and organs [15][16][17][18][19][20] . However, the database on deep and persistent toxicity, carcinogenicity, genotoxicity, reproductive toxicity, besides skin or eye irritation and sensitization is very inadequate or even missing.…”
mentioning
confidence: 99%
“…While ROS are components of cell signaling and phagocytosis of foreign material under normal physiologic conditions, their overabundance can induce oxidative stress and reduce viability. Particulate-cell interactions have been shown to induce a variety of ROS-mediated damage, including mitochondrial dysfunction (Alshatwi et al, 2013), DNA damage (Nabeshi et al, 2011;Olgun et al, 2017), membrane damage autophagy (Li et al, 2010), apoptosis (Hiura et al, 1999), and genotoxicity (Knaapen et al, 2004). We intend to further investigate this potential mechanism of toxicity in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…In vivo, en modelos de hámster y rata, la exposición a compuestos de In como InP, ITO, In 2 O 3 y óxido de indio (IO) generan inflamación pulmonar (Oda 1997, Yamazaki et al 2000, Tanaka et al 2002, Lison et al 2009, Nagano et al 2011a, Badding et al 2015, Jeong et al 2016. Se ha demostrado in vitro que compuestos y nanopartículas de In en forma de ITO, InP, In 2 O 3 e InCl 3 producen liberación de lactato deshidrogenasa (Lison et al 2009, Tabei et al 2016, Ahamed et al 2017, reducen la viabilidad de manera dosis dependiente (Gwinn et al 2013, Gwinn et al 2015, Tabei et al 2016, Afroz et al 2018, Olgun et al 2017) e inducen apoptosis (Bustamante et al 1997, Badding et al 2014, Tsai et al 2020.…”
Section: Mecanismos De Toxicidad Y Genotoxicidad Del In 3+unclassified
“…Varios compuestos y nanopartículas de In 3+ aumentan la producción de ERO en líneas celulares (Lin et al 2013, Tabei et al 2016, Tsai et al 2020, entre las que se encuentran COOy •OH (Lison et al 2009, Olgun et al 2017. Uno de los mecanismos descritos es el abatimiento de la actividad de la superóxido dismutasa y disminución los niveles de GSH; donde la adición de antioxidantes (N-acetil-cisteína (NAC)) inhibe la generación excesiva de ERO y atenúa el efecto citotóxico provocado por el metal (Ahamed et al 2017).…”
Section: Mecanismos De Toxicidad Y Genotoxicidad Del In 3+unclassified